2018
DOI: 10.1016/j.yexcr.2018.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic changes in clonal descendants of irradiated human fibroblasts

Abstract: To study delayed genetic and epigenetic radiation effects, which may trigger radiation-induced carcinogenesis, we have established single-cell clones from irradiated and non-irradiated primary human fibroblasts. Stable clones were endowed with the same karyotype in all analyzed metaphases after 20 population doublings (PDs), whereas unstable clones displayed mosaics of normal and abnormal karyotypes. To account for variation in radiation sensitivity, all experiments were performed with two different fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 106 publications
1
35
0
Order By: Relevance
“…Aging is associated with hypo‐ and hypermethylation events at specific regions of the genome (Unnikrishnan et al, ). Recently, we showed that the methylation of various repeat families decreased, whereas that of rDNA increased during in vitro aging of fibroblast clones (Flunkert et al, ). Here, we used the same bisulfite pyrosequencing assays to quantify mean methylation of ALU, LINE1, and α‐satellite repeats in WRN ‐, LMNA ‐, and POLD1 ‐mutant patients and controls (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is associated with hypo‐ and hypermethylation events at specific regions of the genome (Unnikrishnan et al, ). Recently, we showed that the methylation of various repeat families decreased, whereas that of rDNA increased during in vitro aging of fibroblast clones (Flunkert et al, ). Here, we used the same bisulfite pyrosequencing assays to quantify mean methylation of ALU, LINE1, and α‐satellite repeats in WRN ‐, LMNA ‐, and POLD1 ‐mutant patients and controls (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Perturbations of this highly organized process cause nucleolar stress that is involved in the pathogenesis of many human diseases including cancer, and metabolic and cardiovascular disorders (Wang et al, ). Impaired ribosome biogenesis (Rattan, ) and rDNA hypermethylation (Flunkert et al, ) have also been linked to aging. During in vitro aging of fibroblasts, rDNA hypermethylation was reported to be more pronounced in two WS patients, compared with four controls (Machwe, Orren, & Bohr, ).…”
Section: Discussionmentioning
confidence: 99%
“…84 A good example of the valuable contribution of studies using normal cells is coming from a recent study carried out using normal fibroblasts. 85 Clonal cell populations generated from cells treated with low doses of IR displayed clusters of CNVs at FRA3B and FRA7J. 85 Interestingly, three CNVs, affecting directly or indirectly the FHIT gene, were detected in clones showing karyotypic instability.…”
Section: Evolutionary Conservation Of Cfssmentioning
confidence: 99%
“…85 Clonal cell populations generated from cells treated with low doses of IR displayed clusters of CNVs at FRA3B and FRA7J. 85 Interestingly, three CNVs, affecting directly or indirectly the FHIT gene, were detected in clones showing karyotypic instability. At the same time, the majority of cell clones derived from irradiated cells did not exhibit genomic alterations at FHIT, 85 although FRA3B is a well-known hot spot for radiation-induced fragility.…”
Section: Evolutionary Conservation Of Cfssmentioning
confidence: 99%
See 1 more Smart Citation